Design, Molecular Docking, and in Silico Analysis of Analogues of Chloroquine, and Hydroxychloroquine Against Sars-Cov-2 Target (6W63.pdb) - SN, Yakubu; CO, Poyi; EO, Afolabi (Archives of Clinical and Biomedical Research, 2021)
Computer-aided drug design has been an effective strategy and approach to discover, develop, analyze, accelerate, and economize design, and development of drugs and biologically active molecules. A total of twelve analogues of Chloroquine (CQ) and Hydroxychloroquine (HCQ) were designed and virtually analyzed using PyRx software, Molinspiration, Swiss ADME, Swiss-Target Prediction software, and ProTox-II-Prediction of toxicity platform. Based on the docking studies carried out using Autodock vina, five analogues; H-368 (-6.0Kcal/mol), H-372 (-6.0Kcal/mol), H-156 (-5.9Kcal/mol), H-139 (-5.7Kcal/mol), C-136 (-5.7Kcal/mol) exhibited higher binding affinity compared to HCQ (-5.5Kcal/mol), while all twelve analogues exhibited higher binding affinity compared to CQ (-4.5Kcal/mol). In silico analysis of toxicity profile of these analogues shows a lower potential to toxicity and a comparable activity on some major isoforms of cytochrome P450. But unlike the parent molecules, both H-139 and H-156 are substrates of P-glycoproteins (P-gp) which implies that these analogues possess high clearance and less pharmacokinetic-related drug-drug interactions compared to the parent molecules. Herein we propose these analogues as potential inhibitors or lead compounds against SARS- CoV-2 with a view of synthesizing them, conducting more molecular dynamic simulations, and conducting In vitro studies on them.